Impact of pseudoprogression and treatment beyond progression on outcome in patients with non-small cell lung cancer treated with immune checkpoint inhibitors. (1st January 2020) - Won, Sang Eun; Park, Hyo Jung; Byun, Sangil; Pyo, Junhee; Kim, Jwa Hoon; Choi, Chang-Min; Lee, Jae Cheol; Lee, Dae Ho; Kim, Sang-We; Yoon, Shinkyo; Kim, Kyung Won
ABSTRACT: Background: Immune checkpoint inhibitors (ICI) have become an important treatment option for non-small cell lung cancer (NSCLC). We aimed to evaluate the clinical impact of pseudoprogression (PsP) and treatment beyond RECIST1.1-defined progressive disease (TBP) on outcome in NSCLC patients treated with ICI. Methods: NSCLC patients treated with ICI between Mar 2016 and July 2018 were recruited in a consecutive manner. Response was assessed every 8–12 weeks using RECIST1.1 and iRECIST. Based on iRECIST, PsP was defined as progressive disease (PD) on RECIST1.1 subsequently reset to non-PD categories. Using log-rank test, progression-free survival (PFS) was compared between patients with and without PsP, and overall survival (OS) was compared between patients treated with and without TBP. The impact of TBP on OS was evaluated through multivariate Cox proportional hazard models. Results: Of the 189 patients, seven (3.7%) experienced PsP which mostly occurred approximately 3 months after baseline. The median PFS was significantly longer in patients with PsP (not reached) than those without PsP (3.8 months, P = .02). Among patients who demonstrated PD according to RECIST1.1, median OS was significantly longer in patients with TBP (17.2 months) than those without TBP (7.4 months, P < .001). On multivariate analysis adjusting other covariates, TBP (HR, 0.4; 95% CI, 0.2–0.7) remained as a significant protective factor for mortality. Conclusion: PsP occurred in 3.7% of NSCLC patients under ICI treatment. Based on iRECIST scheme, PsP and TBP may be associated with survival benefit.